Walking : connecting sustainable transport with health - Mulley, Corinne; Gebel, Klaus; Ding, Ding active 2017 (Transport and sustainability ;, 2017)
This book combines core chapters on different aspects of sustainable transport and health, together with case studies of particular approaches to synthesise walking and health in cities around the globe. Walking as a research area is multifaceted and this book presents chapters which synthesise the current state of research and practice, which will be of interest to readers, both academic and professional, and point to areas that will feature prominently in future research domains. Although the links between transport and health have long been recognised in the transport and health disciplines separately, it is a fairly recent phenomenon that they have been seen as a legitimate inter- and multi-disciplinary area. The areas of intersection have become more obvious with better understanding between the different disciplines with mutual and explicit understanding that great benefits come from recognising synergies between disciplinary approaches to similar problems. The connections between walking and health have benefited from a better understanding of the contributions of different disciplines.This book exploits this multidisciplinary approach.- Resumé vydavatel